2014
DOI: 10.1177/0954405414530900
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional variation stream modeling of investment casting process based on state space method

Abstract: Investment casting process produces high-precision castings, but there is a constant demand for improving the process capabilities, including dimensional accuracy and consistency. In this article, a state space modeling approach of investment casting process for dimensional variation is developed. This research focuses on the linear dimensional change (expansion or shrinkage) in the investment casting process. The generation, propagation and accumulation of the dimensional variation in the investment casting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…12 Hence, it is necessary to investigate each stage of the ICP, including the wax pattern injection of the ceramic core and blades, core deflection, and the DS process. Liu 11 established the state space model to describe the accumulation and transmission of the variation. The system transmitting matrix A(k) expresses the relationship between previous stages and the current stage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Hence, it is necessary to investigate each stage of the ICP, including the wax pattern injection of the ceramic core and blades, core deflection, and the DS process. Liu 11 established the state space model to describe the accumulation and transmission of the variation. The system transmitting matrix A(k) expresses the relationship between previous stages and the current stage.…”
Section: Introductionmentioning
confidence: 99%
“…Within these stages, many smaller processes are involved, such as die construction, wax injection, slurry coating and stuccoing, dewaxing, roasting, and casting. 11 All these stages have their own complexities and pose a potential and uncertain risk to the accuracy of the dimensions of the final part. Furthermore, not only does the process of producing the blade casting cause volume shrinkage, but the variation in the geometric features also obeys a certain pattern, resulting in deformation and dimensional deflection of the casting.…”
Section: Introductionmentioning
confidence: 99%
“…Investment casting is an important industry expertise and has been widely used in various manufacturing fields due to its advantages of high precision, high shape complexity, and good adaptability to various alloys. [1][2][3] Singh and Singh 4 reviewed the development of this technique and demonstrated that the main steps of investment casting include wax mold pressing and assembly, mold preparation, dewaxing and mold baking, liquid metal pouring, mold cleaning and posttreatment of castings.…”
Section: Introductionmentioning
confidence: 99%
“…Among the models of multistation assembly variation propagation, the state space method 16,17 and stream of variation methodology 18 are explored in much greater depth due to their linear structure and the automatic handling of complicated stage-wise interaction. In aircraft assembly process, assembly variation is affected not only by positioning, clamping, 19 joining 2,3,13,20 and so on, but also by part distortion in manufacture.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the focus of variation analysis of the multi-station hierarchical assembly processes is the establishment of the relationship between the tolerances of process elements across multiple stages and the variation of the final product. Among the models of multi-station assembly variation propagation, the state space method 16,17 and stream of variation methodology 18 are explored in much greater depth due to their linear structure and the automatic handling of complicated stage-wise interaction. In aircraft assembly process, assembly variation is affected not only by positioning, clamping, 19 joining 2,3,13,20 and so on, but also by part distortion in manufacture.…”
Section: Introductionmentioning
confidence: 99%